Теоретические основы развития функциональной грамотности - Шалгимбекова, А.Б.; Молдабаева, С.А. (My University, 2016)
The bases of forming and development of functional literacy of man, related to the capture to them functional knowledge, open up in this article in theory
Keywords: functional literacy; base education; totality of functions functional literacy; adaptive; preparatory; vocational; orientation; educator; development